An application of the theory of planned behaviour to study the influencing factors of participation in source separation of food waste. - Wan Ab. Karim Ghani, Wan Azlina; Idris, Azni; Awang Biak, Dayang Radiah; Rusli, Iffah Farizan (2013)
Tremendous increases in biodegradable (food waste) generation significantly impact the local authorities, who are responsible to manage, treat and dispose of this waste. The process of separation of food waste at its generation source is identified as effective means in reducing the amount food waste sent to landfill and can be reused as feedstock to downstream treatment processes namely composting or anaerobic digestion. However, these efforts will only succeed with positive attitudes and highly participations rate by the public towards the scheme. Thus, the social survey (using questionnaires) to analyse public's view and influencing factors towards participation in source separation of food waste in households based on the theory of planned behaviour technique (TPB) was performed in June and July 2011 among selected staff in Universiti Putra Malaysia, Serdang, Selangor. The survey demonstrates that the public has positive intention in participating provided the opportunities, facilities and knowledge on waste separation at source are adequately prepared by the respective local authorities. Furthermore, good moral values and situational factors such as storage convenience and collection times are also encouraged public's involvement and consequently, the participations rate. The findings from this study may provide useful indicator to the waste management authorities in Malaysia in identifying mechanisms for future development and implementation of food waste source separation activities in household programmes and communication campaign which advocate the use of these programmes.